Core Outcome Domains for early phase clinical trials of sound-, psychology-, and pharmacology-based interventions to manage chronic subjective tinnitus in adults: The COMIT'ID study protocol for using a Delphi process and face-to-face meetings to establish consensus - Fackrell, K. (2017)
Background: The reporting of outcomes in clinical trials of subjective tinnitus indicates that many different tinnitus-related complaints are of interest to investigators, from perceptual attributes of the sound (e.g. loudness) to psychosocial impacts (e.g. quality of life). Even when considering one type of intervention strategy for subjective tinnitus, there is no agreement about what is critically important for deciding whether a treatment is effective. The main purpose of this observational study is, therefore to, develop Core Outcome Domain Sets for the three different intervention strategies (sound, psychological, and pharmacological) for adults with chronic subjective tinnitus that should be measured and reported in every clinical trial of these interventions. Secondary objectives are to identify the strengths and limitations of our study design for recruiting and reducing attrition of participants, and to explore uptake of the core outcomes. Methods: The 'Core Outcome Measures in Tinnitus: International Delphi' (COMIT'ID) study will use a mixed-methods approach that incorporates input from health care users at the pre-Delphi stage, a modified three-round Delphi survey and final consensus meetings (one for each intervention). The meetings will generate recommendations by stakeholder representatives on agreed Core Outcome Domain Sets specific to each intervention. A subsequent step will establish a common cross-cutting Core Outcome Domain Set by identifying the common outcome domains included in all three intervention-specific Core Outcome Domain Sets. To address the secondary objectives, we will gather feedback from participants about their experience of taking part in the Delphi process. We aspire to conduct an observational cohort study to evaluate uptake of the core outcomes in published studies at 7years following Core Outcome Set publication. Discussion: The COMIT'ID study aims to develop a Core Outcome Domain Set that is agreed as critically important for deciding whether a treatment for subjective tinnitus is effective. Such a recommendation would help to standardise future clinical trials worldwide and so we will determine if participation increases use of the Core Outcome Set in the long term. Trial registration: This project has been registered (November 2014) in the database of the Core Outcome Measures in Effectiveness Trials (COMET) initiative. © 2017 The Author(s).